2019
DOI: 10.4103/ijpvm.ijpvm_522_18
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypertension in renal diseases in Iran: Systematic review and meta-analysis

Abstract: Background: Hypertension is a risk factor for renal disease. Therefore, this study was aimed at estimating the prevalence of hypertension in renal patients in Iran through meta-analysis. Methods: The search was carried out using authentic Persian and English keywords in national and international databases including IranMedex, SID, Magiran, IranDoc, Medlib, ScienceDirect, Pubmed, Scopus, Cochrane, Embase, Web of Science, Medline, and Google Scholar search engine without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 50 publications
3
7
0
Order By: Relevance
“…We assessed the risk of CKD associated with these comorbidities in our study population of male patients 12 years and older and found that only hypertension was an independent risk factor for CKD. This finding is consistent with some previous studies that identified hypertension as a main risk factor for CKD [ 7 , 8 , 35 ]. Hypertension is a growing non-communicable disease and an important leading cause of CKD [ 7 , 35 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…We assessed the risk of CKD associated with these comorbidities in our study population of male patients 12 years and older and found that only hypertension was an independent risk factor for CKD. This finding is consistent with some previous studies that identified hypertension as a main risk factor for CKD [ 7 , 8 , 35 ]. Hypertension is a growing non-communicable disease and an important leading cause of CKD [ 7 , 35 ].…”
Section: Discussionsupporting
confidence: 94%
“…This finding is consistent with some previous studies that identified hypertension as a main risk factor for CKD [ 7 , 8 , 35 ]. Hypertension is a growing non-communicable disease and an important leading cause of CKD [ 7 , 35 ]. Hypertension accelerates the decline of renal function regardless of aetiology [ 8 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…According to the Centers for Disease Control and Prevention, in 2014, more than 20% of people with serious hypertension suffered from chronic kidney disease and were at risk for ESRD. On the other hand, hypertension is present in over 90% of individuals with advanced kidney disease [327], [330]. In all developed countries and in many developing countries, diabetes and hypertension are considered as the main cause of CKD.…”
Section: Renal Failurementioning
confidence: 99%
“…We read with great interest the review article “Prevalence of Hypertension in Renal Diseases in Iran: Systematic Review and Meta-Analysis” by Motedayen et al ., published in Int J Prev Med 2019. [ 1 ]…”
mentioning
confidence: 99%